Editorial: Dissonance Between Formal Policy and Social Reality in Contemporary Governance - Dias Pabyantara Swandita Mahayasa; Arum Tri Utami (JUSS (Jurnal Sosial Soedirman), 2026)
Editorial: Dissonance Between Formal Policy and Social Reality in Contemporary Governance